2008
DOI: 10.1002/lpor.200810003
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐nanoparticle plasmonics

Abstract: The rapid emergence of nanoplasmonics as a novel technology has been driven by recent progress in the fabrication, characterization, and understanding of metal-nanoparticle systems. In this review, we highlight some of the key advances in each of these areas. We emphasize the basic physical understanding and experimental techniques that will enable a new generation of applications in nano-optics. Abstract The rapid emergence of nanoplasmonics as a novel technology has been driven by recent progress in the fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
661
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 703 publications
(674 citation statements)
references
References 195 publications
(235 reference statements)
10
661
0
3
Order By: Relevance
“…Surface plasmon polaritons (SPPs) are electromagnetic surface waves coupled to collective excitations of the free electrons in conductors. When these hybrid excitations occur in conducting nanostructures-such as nanoparticles [8,9] or engineered metamaterials [10,11]the corresponding nonpropagating plasmon polaritons are generally referred to as localized surface plasmons (LSPs) [1]. Perhaps the most alluring property of plasmons is that they exhibit large field enhancements and deep subwavelength confinement of EM fields, thereby circumventing the diffraction limit of conventional optics [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Surface plasmon polaritons (SPPs) are electromagnetic surface waves coupled to collective excitations of the free electrons in conductors. When these hybrid excitations occur in conducting nanostructures-such as nanoparticles [8,9] or engineered metamaterials [10,11]the corresponding nonpropagating plasmon polaritons are generally referred to as localized surface plasmons (LSPs) [1]. Perhaps the most alluring property of plasmons is that they exhibit large field enhancements and deep subwavelength confinement of EM fields, thereby circumventing the diffraction limit of conventional optics [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…LSPR occurs when the frequency of the electric field of the incident light resonates with the oscillations of MNPs conduction electrons. The excited MNPs thereby strongly absorb (near-field effect) and scatter (far-field effect) the incident light, producing an enhancement up to a factor of 100 [3], in the electric field surrounding them [8]. Previous studies showed that the PCE of BHJOSCs was improved considerably by MNPs incorporated into OSC layers either on top of indium tin oxide (ITO) [9][10][11][12], within poly(3,4-ethyl-enedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) [13][14][15], within P3HT:PCBM [16], or with the back electrode [17].…”
mentioning
confidence: 99%
“…Tuning of the LSPR properties can be achieved through synthesis by exploiting differences in nanoparticle size, geometry, surface morphology, aggregation, aspect ratio, and the dielectric constant of the surrounding media [15,33,[35][36][37][38][39][40][41][42][43][44][45]. Since each application relies on a specific set of conditions for optimized efficiency, the structural parameters of the nanoparticles employed for use must be tailored accordingly.…”
Section: Metal Nanostructuresmentioning
confidence: 99%